Functional Inhibitory Siglec-6 Is Upregulated in Human Colorectal Cancer-Associated Mast Cells - Yu, Yingxin; Blokhuis, Bart R. J.; Diks, Mara A. P.; Keshavarzian, Ali; Garssen, Johan; Redegeld, Frank A. (Frontiers in Immunology, 2018)
Mast cells (MC) accumulate in colorectal cancer (CRC) and the relationship between MC density and cancer progression has been well recognized. MC can be either pro-tumor or anti-tumor players, depending on the local factors present in the tumor microenvironment. Upon malignant transformation, cancer cells express high levels of sialic acids on cell membrane or by secretion. Siglecs are a family of immunoglobulin-like receptors that bind sialic acids and each subtype has a distinct pattern of expression on immune cells. Among them, Siglec-6 is expressed predominately by MC. However, the function of Siglec-6 in MC is largely unexplored and whether it is expressed by CRC-associated MC remains unknown. In this study, we explored the function of Siglec-6 in CD34+ derived human MC. MC activation was initiated by IgE crosslinking with or without preincubation of anti-Siglec-6 Ab. Siglec-6 engagement significantly attenuated IgE-dependent MC degranulation as measured by ß-hexosaminidase release and CD63 expression. Interestingly, the production of GM-CSF was also shown reduced upon Siglec-6 engagement. To mimic the milieu of CRC, we cultured primary human MC with colon cancer cells or under hypoxia and Siglec-6 expression was then measured on these conditioned MC. Coculture with colon cancer cells (HT29 and Caco2) induced upregulation of Siglec-6 on MC. In comparison, normal colon cells (CCD841) had no effect. Also, a time-dependent increase of Siglec-6 by MC was observed under 1% O2. Immunohistochemistry of CRC tissue showed expression of Siglec-6 by MC in submucosa. Lectin immunochemistry revealed the presence of actual ligands for Siglec-6 in human CRC tissues. Together, our findings illustrate that Siglec-6 is a functionally inhibitory receptor on MC and suggest that Siglec-6 expression may be relevant for MC activity in the tumor microenvironment of CRC.